Rest tremor and extrapyramidal symptoms after midbrain haemorrhage: clinical and 18F-dopa PET evaluation. Issue 8 (August 1994) - Defer, G L; Remy, P; Malapert, D; Ricolfi, F; Samson, Y; Degos, J D
Abstract : A 25 year old man had an acute subarachnoid haemorrhage due to the rupture of a right peduncular subthalamic arteriovenous malformation. Seven months later he developed a left rest tremor associated with mild bilateral extrapyramidal symptoms and responsive to levodopa treatment. Surface EMG recording showed synchronous activity of agonist and antagonist muscles in the left limbs. A PET 18F-dopa study showed a large decrease of the Ki value in the right striatum. One year after the stroke a persistent postural component developed in the tremor.